2016
DOI: 10.2494/photopolymer.29.273
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitive Polyimide-silicone Copolymer based on Reaction Development Patterning (RDP)

Abstract: Multi-block copolymers between polyester (polyarylate) and polydimethylsiloxane were prepared by polycondensation using polydimethylsiloxane having p-hydroxyphenyl groups at its both chain ends as a diol monomer. The copolymer gave positive-tone fine pattern by the reaction development patterning with developer containing ethanolamine as a nucleophile. The silicone unit hybridized with polyarylate enabled pattern formation from dry film by contributing not only to high photosensitivity but also to high dissolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Accordingly, the photosensitivity or responsibility of photosensitive groups is among the important factors for determining the resolution of micropatterns. 18 So far, numerous photosensitive groups have been used for PSPI, such as t-Boc, 19 DNQ groups, [20][21][22][23] and onitrobenzyl group (Nb) 17,[24][25][26][27][28] derivatives. Among them, Nb derivatives are well-known to be photocleavages by rearrangement mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the photosensitivity or responsibility of photosensitive groups is among the important factors for determining the resolution of micropatterns. 18 So far, numerous photosensitive groups have been used for PSPI, such as t-Boc, 19 DNQ groups, [20][21][22][23] and onitrobenzyl group (Nb) 17,[24][25][26][27][28] derivatives. Among them, Nb derivatives are well-known to be photocleavages by rearrangement mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Polyimide (PI) is one of the high-performance polymers. It exhibits excellent thermal, electrical, and mechanical properties, and consequently, it has been widely used in aerospace, electronics, and other industries. PI can be copolymerized with a polyamide. The commercial polyamideimide (PAI) with the brand name of TorlonVR 4000TF has the superior properties of both polyamides and PIs, such as high mechanical strength, thermal resistance, and wide chemical resistance; hence, there are many developments for its application, including gas separation, nanofiltration, osmotic power generation, pervaporation, and so forth .…”
Section: Introductionmentioning
confidence: 99%
“…Organic polymer/silica hybrids often increase thermal stability, surface planarity and optical transparency as compared with the corresponding organic polymers [12][13][14]. In our previous work, PI-silicone copolymer afforded negative-tone pattern by RDP using tetramethylammonium hydroxide/water/NMP/methanol as developer [15]. The successful pattern formation probably indicated that RDP could be applied to any hybrid copolymers containing (-C(O)-X-) bonds.…”
Section: Introductionmentioning
confidence: 99%